Milking-time test : methodology and assessment of vacuum recordings during machine milking of dairy cows - Lazović, Dragana (SLU/Dept. of Animal Nutrition and Management (until 231231), 2016)
The aim of the study was to improve the basic understanding and the methodology of routine milking-time testing by determining the required sampling frequency and number of cows and milkings needed to be measured in order to yield representative results. Milking-time tests represent the most direct method to validate the system vacuum of a milking machine, both the aptitude of vacuum production and the vacuum regulation throughout the system. The vacuum was measured at five points along the milking machine in a milking parlour for six consecutive days, both during morning and evening milking. Three points were measured continuously during the whole milking session, the receiver and two points on the milkline, while the claw and the mouthpiece chamber vacuum (MPCV) was measured during the milking of six cows on each milking occasion. Data was collected at a frequency of 100 Hz and the possibility of obtaining equally reliable results of the milking-time tests with a lower sampling frequency of 10 Hz and 1 Hz was tested in the data analysis by using subsamples of the complete dataset. The sampling frequency of 10 Hz compared to the 100 Hz frequency gave reliable results for means of the claw vacuum and MPCV while the frequency of 1 Hz did not. The number of cows and milkings needed to be measured in order to yield representative results could not be determined without further data analysis.